JORDAN: A PALACE COUP?. Issue 3 (27th May 2021) - Millett, Peter
Abstract: This article provides an overview of the internal and external political and economic problems facing the Middle-Eastern Kingdom of Jordan in the light of the so-called 'attempted coup' of Prince Hamzeh which took place at the beginning of April 2021. It then discusses a number of key factors which may affect Jordan's future prospects.